Cardiovascular risk factors in patients hospitalized for COVID-19 - Mejía-Zambrano, Henry (2022)
Objective: To determine cardiovascular risk factors in patients hospitalized for COVID-19. Material and methods: Systematic review that includedobservational studies with cardiovascular disease risk factors in patients hospitalized with COVID-19, with text available, in English or Spanish; letters to the editor, abstracts, documents and clinical trials were excluded, studies without reliable data and duplicate sources. A bibliographic search of literature was conducted in PubMed, MEDLINE and JAMA, from June 12 to 18, 2021, search strategies were evaluated through the program of the Cochrane Manual of systematic reviews. The Mendeley program was used to manage bibliographic references and eliminate studies. The methodological quality of articles was evaluated with tools from the National Heart, Lung and Blood Institute (NHLBI), and an overall rating of 75 % good, 50-75 % regular, < 50 % bad was provided. Results: From 400 articles, 10 cohort studies, 3 retrospective studies, 1 prospective study, and 1 systematic review and meta-analysis were selected. The risk factors for cardiovascular disease in patients hospitalized with COVID-19 in this systematic review were: 46% of patients had high blood pressure (HTN); 2 1 % had diabetes mellitus; 15 % had dyslipidemia; 10% had chronic kidney disease (CKD); 6%, myocardial infarction (AMI); 5%, morbid obesity; 4%, chronic heart failure (CHF) andatrial fibrillation (AF); and 3 %, cerebrovascular disease (CVD). Conclusion: The main risk factors for cardiovascular disease in patients hospitalized for COVID-19 were: hypertension, diabetes mellitus, dyslipidemia, myocardial infarction and obesity.